Study of Solar Combined Air Energy Greenhouse Heating System Model - Hao, Wang; Jintao, Wei; Ruifeng, Zhang; Zhenjun, Xu (Frontiers in Energy Research, 2022)
This paper analyzesd the distribution characteristics of solar energy resources and solar combined air energy greenhouse heating system, established and solved the mathematical model of solar combined air energy greenhouse heating system, calculatinged solar heat collection and solar heating energy consumption. From the data analysis, the relationship between the heat gain power, heating power and the water temperature of the water storage tank of the heat pump system were obtained. The mathematical model of solar combined air energy greenhouse heating system water storage tank was solved, and then the operating condition and volume of solar combined air energy greenhouse heating system water storage tank arewere determined. It also analyzesd the solar heat collection and solar heating energy consumption in Qingdao, pointsed out the advantages of solar combined air energy greenhouse heating system and finally obtained the best heating scheme.